(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, one of the leading representatives of Uzbek literature, It was published after the death of Abdulla Oripov, the poems included in the poetry collection "The Birth of a Poet" describe the mental state of a person, emotional experiences, or values unique to the Uzbek people.